The Role Of The Board Commissioners In The Implementation Of The Principles Of Good Corporate Governance And The Achievement Of The Performance Of Bank Perkreditan Rakyat In Tasikmalaya - Dedi Kusmayadi; Iwan Hermansyah (Jurnal Akuntansi, 2018)
This study aims to determine: the effect of the role of the commissioners, to the implementation of the principles of good corporate governance, the influence of the role of the commissioners and the implementation of the principles of corporate governance either partially or simultaneously on the performance of Bank Perkreditan Rakyat in Tasikmalaya. The method used a quantitative descriptive study population is a Bank Perkreditan Rakyat in Tasikmalaya, sampling using purposive sampling technique, with analysis tools using path analysis. The results showed that: the role of the board of commissioners, the implementation of the principles of corporate governance and bank performance generally categorized as good; the role of commissioner to the application of the principles of good corporate governance positively and significantly; and, the role of the commissioner and the application of the principles of good corporate governance partially and simultaneously on the performance of positive and significant influence.